The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1186/s12910-022-00870-0
|View full text |Cite
|
Sign up to set email alerts
|

Differences between doctors of medicine and dental medicine in the perception of professionalism on social networking sites: the development of the e-professionalism assessment compatibility index (ePACI)

Abstract: Background Social networking sites (SNSs) have penetrated all aspects of health care professionals’ (HCPs’) professional and private lives. A new term, e-professionalism, has emerged, which describes the linking of traditional values with this new dynamic online environment for HCPs. The four aims of this study were: (1) to examine their SNS prevalence and usage habits, (2) to examine their perception of e-professionalism, (3) to develop an e-professionalism assessment compatibility index and (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 55 publications
0
11
1
Order By: Relevance
“…Previous research on the same sample [ 34 ] showed a significant difference in age, where MDs were older than DMDs with an average age of 39.26 years as opposed to 36.58 years, respectively, and in the type of employment, with more than two-thirds of DMDs (168/246, 68.2%) being employed in the private sector compared with only 20.5% (104/507) of MDs. All specialization status levels are included in the sample ( Multimedia Appendix 3 ).…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…Previous research on the same sample [ 34 ] showed a significant difference in age, where MDs were older than DMDs with an average age of 39.26 years as opposed to 36.58 years, respectively, and in the type of employment, with more than two-thirds of DMDs (168/246, 68.2%) being employed in the private sector compared with only 20.5% (104/507) of MDs. All specialization status levels are included in the sample ( Multimedia Appendix 3 ).…”
Section: Resultsmentioning
confidence: 90%
“…One potential extension of this study, which could lead to a more thorough understanding of the topic, involves testing the indexes on specific subsamples, particularly within specialties such as dermatology and reconstructive and cosmetic surgery. These specialties may involve visual representations of procedures, such as “before and after” images [ 34 ], which could pose potential threats to e-professionalism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Talking of digital pro ciency, although digital natives assumed that they were well equipped with digital literacy, the published body of literature depicted a contradictory picture (17,61,74,75). Gettig (26) identi ed two contrasting perspectives, students having a laxed approach while posting online content in a personal capacity while faculty believed in professionalism irrespective of personal and professional capacity.…”
Section: Resultsmentioning
confidence: 99%
“…Subsequently, Marelić et al translated and modified this instrument for use in the Croatian language ( 13 ). Viskić et al introduced the ePACI index, derived from responses to the White et al instrument ( 20 ). The theoretical spectrum of this index extends from -1 to +1.…”
Section: Participants and Methodsmentioning
confidence: 99%